Morphological Characterization and Phytochemical Analysis of Moringa Plant (Moringa oleifera L.) Different Altitudes in Bali - Danga, Jeni Rambu Yaku; Rai, I Nyoman; Dwiyani, Rindang (Universitas Panji Sakti, 2025)
The Moringa plant (Moringa oleifera L.) is a plant that has many benefits and has long been used by various groups throughout the world. Almost all parts of this magical plant can be used for multiple purposes. Moringa plants spread and adapt to different environments, increasing phenotypic and phytochemical diversity. The research was conducted at three altitudes in Bali, lowlands, medium, and highlands from December 2023–May 2024. The study was conducted to determine differences in morphological characters and phytochemical content of Moringa plants. This research used UPGMA analysis to determine the relationship based on morphological characters, flavonoids, tannins, and vitamin E using a UV-Vis Spectrophotometer, while the antioxidant activity test was carried out using the DPPH method. The results of the identification of morphological characters showed differences in qualitative characters, which were seen in leaf color and flower color, while quantitative characters were seen in leaf length, leaf thickness, pod length, and number of seeds. Nine Moringa accessions showed differences in phytochemical content. The highest flavonoid and vitamin E content in the lowlands are (599.961 mg QE/100 g) and (599.961 mg QE/100 g), tannins in the medium plains (368.140 mg TAE/100 g), and the highest IC50 in the highlands (54.94 ppm).